2021
DOI: 10.1136/bmjopen-2020-048007
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of the Medical Examiner role in identifying problems with the quality of patient care

Abstract: ObjectiveA national system of Medical Examiners (MEs) implemented in England and Wales from April 2019 was intended to ensure that every death receives scrutiny from an independent, senior doctor, resulting in early detection of problems in care. The aim of this study was to increase understanding of how the ME role operates to identify problems related to quality of patient care and to explore the potential for development to maximise learning opportunities.DesignA qualitative approach involved the use of sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This could be due in part to NSCTs increasing awareness of the LfDs guidance for NHS trusts on working with bereaved families and carers, 8 more likely though is because of the increased establishment of ME Systems supporting the bereaved within NSCTs. 707 Further recognition of the need for and provision of training for healthcare staff with regard to bereaved relatives was identified by a few NSCTs. Despite evidence that patient and family engagement improve patient safety, many organisations still have difficulties achieving this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due in part to NSCTs increasing awareness of the LfDs guidance for NHS trusts on working with bereaved families and carers, 8 more likely though is because of the increased establishment of ME Systems supporting the bereaved within NSCTs. 707 Further recognition of the need for and provision of training for healthcare staff with regard to bereaved relatives was identified by a few NSCTs. Despite evidence that patient and family engagement improve patient safety, many organisations still have difficulties achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…There was an increase in reporting of ‘Lack of/problem with engagement with/support of families/carers’ from 4% in 2017/2018 to 28% in 2019/2020. This could be due in part to NSCTs increasing awareness of the LfDs guidance for NHS trusts on working with bereaved families and carers,8 more likely though is because of the increased establishment of ME Systems supporting the bereaved within NSCTs 707. Further recognition of the need for and provision of training for healthcare staff with regard to bereaved relatives was identified by a few NSCTs.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due in part to NSCTs increasing awareness of the LfDs guidance for NHS trusts on working with bereaved families and carers, [8] more likely though is because of the increased establishment of Medical Examiner Systems supporting the bereaved within NSCTs. [44] Further recognition of the need for and provision of training for healthcare staff with regards to bereaved relatives was identified by a few NSCTs. Despite evidence that patient and family engagement improve patient safety, many organisations still have difficulties achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the current development across the UK of Medical Examiners (distinct to the American coroner role of the same name) offers promise, encompassing case-note review, discussion with the attending doctor and separately with the deceased's next of kin for all deaths (apart from those requiring compulsory referral to a Coroner such as suicide, trauma and sudden death). 78 Reviews of the UK ME initiative have already demonstrated the usefulness of incorporating next-of-kin views for identifying challenges in community end-of-life care provision 79 and in quality care at the end-of-life during the COVID-19 pandemic. 80 Moving beyond the flawed metric of place of death will not be straightforward, particularly in countries such as the UK where there is no national palliative care data collection system and a decentralised healthcare system.…”
Section: Recommendations and Summarymentioning
confidence: 99%